2009
DOI: 10.1074/jbc.m808491200
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF Regulates the Cellular Response to Hypoxia

Abstract: Hypoxia induces a variety of cellular responses such as cell cycle arrest, apoptosis, and autophagy. Most of these responses are mediated by the hypoxia-inducible factor-1␣. To induce target genes, hypoxia-inducible factor-1␣ requires a chromatin environment conducive to allow binding to specific sequences. Here, we have studied the role of the chromatin-remodeling complex SWI/SNF in the cellular response to hypoxia. We find that SWI/SNF is required for several of the cellular responses induced by hypoxia. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 49 publications
8
104
0
2
Order By: Relevance
“…21 SWI/SNF, which can play a role in both enhancement and repression of gene transcription, was shown to directly bind the HIF-1α promoter and the BAF57 subunit of SWI/SNF was essential for hypoxia induced HIF-1α expression. Kenneth et al also revealed that the SWI/SNF chromatin remodeling complex was required for hypoxia-induced cell cycle arrest.…”
Section: Methylation In Hypoxiamentioning
confidence: 99%
“…21 SWI/SNF, which can play a role in both enhancement and repression of gene transcription, was shown to directly bind the HIF-1α promoter and the BAF57 subunit of SWI/SNF was essential for hypoxia induced HIF-1α expression. Kenneth et al also revealed that the SWI/SNF chromatin remodeling complex was required for hypoxia-induced cell cycle arrest.…”
Section: Methylation In Hypoxiamentioning
confidence: 99%
“…It has been reported that hypoxia induces cell cycle arrest, 38,39 and cell cycle arrest is one of the important factors for chemoresistance of cancer cells. 39,45 However, in our study, the cell cycle distribution differences between cells under normoxia and hypoxia were not meaningful by statistical analysis (Fig.…”
Section: -5mentioning
confidence: 99%
“…But how does it work? As hypoxia can induce cell cycle arrest, 38,39 whether the attenuated chemosensitivity under hypoxia attributes to the blocked cell cycle, especially in G 0 /G 1 . Contrary to our expectation, cell cycle analysis by flow cytometric measurement of DNA content revealed that, though there was a difference in cell cycle distribution between cells under hypoxia and normoxia, it is not meaningful by statistical analysis (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1␣ связывается с чув-ствительными элементами гипоксии в промотерных и уси-ливающих регионах генов-мишеней, способствуя образо-ванию гипоксически индуцируемого фенотипа [56]. Однако, в свою очередь, экспрессия HIF сама может быть пред-метом эпигенетических регуляций, причем всех механиз-мов (метилирования/деметилирования ДНК, модификации гистонов и микроРНК), что было доказано целым рядом последних исследований [57][58][59][60][61]. Кроме того, помимо HIF имеются и другие факторы, вовлеченные в гипоксическую эпигенетическую регуляцию и формирование чувствитель-ного к гипоксии фенотипа.…”
Section: вопросы современной педиатрииunclassified